DIGITALISASI PEMBELAJARAN BIPA MELALUI PENERAPAN IMMERSIVE LEARNING BERBASIS BUDAYA LOKAL SUMATERA UTARA - Cinta; Jessica Ribkha Lumbantobing; Lamtio Patricia Tambunan; Elly Nanda Sinaga; Musyahid Ali; Isda Pramuniati (Smart Education, 2026)
Abstract: Indonesian Language for Foreign Speakers (BIPA) plays an important role in introducing Indonesian language and culture to the world. However, conventional BIPA learning is often less engaging and has not yet utilized the potential of digital technology. This research aims to develop an immersive learning-based BIPA model that integrates elements of North Sumatra's local culture, such as music, dance, and typical cuisine. This study uses the Research and Development (R&D) approach to analyze needs, create teaching materials based on Augmented Reality (AR), and conduct trials with BIPA foreign language learners. The result is a digital paperback that interactively displays local cultural vocabulary and phrases. This innovation demonstrates novelty in combining AR technology with local cultural context. This research concludes that a culture-based digital approach can enrich the learning experience and is recommended for implementation in BIPA teaching across various regions of Indonesia. Keywords: BIPA, Immersive Learning, Digitalization, Local Culture, North Sumatra. Abstrak: Bahasa Indonesia bagi Penutur Asing (BIPA) berperan penting dalam memperkenalkan bahasa dan budaya Indonesia ke dunia. Namun, pembelajaran BIPA konvensional kerap kurang menarik dan belum memanfaatkan potensi teknologi digital. Penelitian ini bertujuan mengembangkan model pembelajaran BIPA berbasis immersive learning yang mengintegrasikan unsur budaya lokal Sumatera Utara, seperti musik, tari, dan kuliner khas. Menggunakan metode Research and Development (R&D), penelitian ini meliputi analisis kebutuhan, perancangan bahan ajar berbasis Augmented Reality (AR), serta uji coba pada peserta didik asing BIPA. Hasilnya berupa livre de poche digital yang menampilkan kosakata dan frasa budaya lokal secara interaktif. Inovasi ini menunjukkan kebaruan dalam menggabungkan teknologi AR dengan konteks budaya daerah. Penelitian ini menyimpulkan bahwa pendekatan digital berbasis budaya mampu memperkaya pengalaman belajar dan direkomendasikan untuk diterapkan dalam pengajaran BIPA di berbagai daerah Indonesia. Kata kunci: BIPA, Immersive Learning, Digitalisasi, Budaya Lokal, Sumatera Utara.